Specific synaptic input strengths determine the computational properties of excitation-inhibition integration in a sound localization circuit - Gjoni, E; Zenke, F; Bouhours, B; Schneggenburger, R (John Wiley and Sons, Inc., 2018)
During the computation of sound localization, neurons of the lateral superior olive (LSO) integrate synaptic excitation arising from the ipsilateral ear with inhibition from the contralateral ear. We characterized the functional connectivity of the inhibitory and excitatory inputs onto LSO neurons in terms of unitary synaptic strength and convergence. Unitary IPSCs can generate large conductances, although their strength varies over a 10-fold range in a given recording. By contrast, excitatory inputs are relatively weak. The conductance associated with IPSPs needs to be at least 2-fold stronger than the excitatory one to guarantee effective inhibition of action potential (AP) firing. Computational modelling showed that strong unitary inhibition ensures an appropriate slope and midpoint of the tuning curve of LSO neurons. Conversely, weak but numerous excitatory inputs filter out spontaneous AP firing from upstream auditory neurons.The lateral superior olive (LSO) is a binaural nucleus in the auditory brainstem in which excitation from the ipsilateral ear is integrated with inhibition from the contralateral ear. It is unknown whether the strength of the unitary inhibitory and excitatory inputs is adapted to allow for optimal tuning curves of LSO neuron action potential (AP) firing. Using electrical and optogenetic stimulation of afferent synapses, we found that the strength of unitary inhibitory inputs to a given LSO neuron can vary over a ∼10-fold range, follows a roughly log-normal distribution, and, on average, causes a large conductance (9 nS). Conversely, unitary excitatory inputs, stimulated optogenetically under the bushy-cell specific promoter Math5, were numerous, and each caused a small conductance change (0.7 nS). Approximately five to seven bushy cell inputs had to be active simultaneously to bring an LSO neuron to fire. In double stimulation experiments, the effective inhibition window caused by IPSPs was short (1-3 ms) and its length depended on the inhibitory conductance; an ∼2-fold stronger inhibition than excitation was needed to suppress AP firing. Computational modelling suggests that few, but strong, unitary IPSPs create a tuning curve of LSO neuron firing with an appropriate slope and midpoint. Furthermore, weak but numerous excitatory inputs reduce the spontaneous AP firing that LSO neurons would otherwise inherit from their upstream auditory neurons. Thus, the specific connectivity and strength of unitary excitatory and inhibitory inputs to LSO neurons is optimized for the computations performed by these binaural neurons.